(untitled) (Research, Society and Development, 2020)
The objective of this study was to evaluate the performance, carcass yield and economic indices of different types of supplementation in the termination of Nellore cattle reared in a pasture system. Thirty-four cattle, with an average weight of 480.4±34.6 kg, submitted to two treatments, animals fed protein-energy supplementation and fed only with energy supplementation, distributed in a completely randomized design, where each animal was considered an experimental repetition. In relation to performance, dry matter consumption in absolute value and in relation to weight, total weight gain, daily weight gain, final weight, hot carcass weight and carcass yield were evaluated. To obtain the economic indices, the revenue of the commercialization and net income per animal were generated from the performance and market price data. The data were submitted to variance analysis and for the medias applied the F. Test There was difference for the average daily gain and the total weight gain. The animals that received the energy supplement had higher average daily gain (1,422 kg/day) compared to animals receiving the protein-energy supplement (0.940 kg/day), which reflected in greater final weight, but profitability was similar (R 170.23 and R 149.53 per animal). Regarding the other variables, there was no effect of the different supplementations. Therefore, the economic return in relation to nutritional investment in the termination of nellore cattle reared in pasture is similar between protein-energy and energy supplementation.